2015
DOI: 10.1152/ajplung.00094.2015
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gelsolin improves lung host defense against pneumonia by enhancing macrophage NOS3 function

Abstract: Yang Z, Chiou TT, Stossel TP, Kobzik L. Plasma gelsolin improves lung host defense against pneumonia by enhancing macrophage NOS3 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 30 publications
2
50
0
Order By: Relevance
“…However, a previous study showed that plasma GSN improves host lung defense against pneumonia by enhancing macrophage NOS3 function [31]. We suggest that the functions of macrophages inhibited or enhanced by GSN are dependent on the specific inflammatory scenario.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, a previous study showed that plasma GSN improves host lung defense against pneumonia by enhancing macrophage NOS3 function [31]. We suggest that the functions of macrophages inhibited or enhanced by GSN are dependent on the specific inflammatory scenario.…”
Section: Discussionmentioning
confidence: 70%
“…GSN is required for macrophage recruitment during re-myelination of the peripheral nervous system [16], and plasma gelsolin improves lung defense against pneumonia by enhancing macrophage NOS3 function [17]. The relationship between macrophages and GSN is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Serum proteins in the alveoli that inhibit surfactant activity (21), together with the paucity of phospholipids, creates mechanical stress that causes parenchymal damage. Many of the serum proteins identified in BALF recruit and activate inflammatory cells (26,27). Thus, both mechanical forces and inflammation likely contribute to the alveolitis and ensuing respiratory failure seen after the loss of ABCA3.…”
Section: Discussionmentioning
confidence: 99%
“…AGER, S100A9, CD14, IL1RAP, SPP1, and SerpinA1 mediate macrophage or neutrophil recruitment and activation, whether derived from inflammatory or parenchymal cells (28)(29)(30)(31)(32). Serum proteins that activate macrophages were present in the BALF, including albumin, AGT, SerpinF1, GSN, GC, HRG, and KNG1 (27,(33)(34)(35). RNA analysis of isolated alveolar epithelial cells from the Abca3-deleted mice indicated increased expression of RNAs associated with cell injury and induced inflammatory response, including IL-33.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang et al found that Plasma gelsolin improves lung host defense against pneumonia by enhancing macrophage NOS3 function. [14].…”
Section: Introductionmentioning
confidence: 99%